The current state of staff development and training at a higher educational institution in Namibia - NARIS, Sylvia N.; UKPERE, Wilfred I. (Annals of Spiru Haret University. Economic Series, 2012)
The paper intends to evaluate the current state of staff development and training at tertiary educational institutions, with special emphasis on Namibia. The research adopted a meta-analytical study, which relied on secondary data. A qualitative research approach was utilised and the emic perspective (author’s view point) was employed. An empirical analysis was utilised in the paper. The authors are of the view that all staff development and training activities should be linked to the strategic goals of organisations. This paper is original since it examines staff development and training activities and various factors affecting it in higher educational institutions, which creates an opportunity for further investigation into strategic issues confronting staff development and training activities in higher education in general.